16S rRNA PCR-Denaturing Gradient Gel Electrophoresis of Oral Lactobacillus casei Group and Their Phenotypic Appearances. (23rd September 2013) - Piwat, S.; Teanpaisan, R.
Abstract : This study aimed to develop a 16S rRNA PCR-denaturing gradient gel electrophoresis (DGGE) to identify the species level of Lactobacillus casei group and to investigate their characteristics of acid production and inhibitory effect. PCR-DGGE has been developed based on the 16S rRNA gene, and a set of HDA-1-GC and HDA-2, designed at V2-V3 region, and another set of CARP-1-GC and CARP-2, designed at V1 region, have been used. The bacterial strains included L. casei ATCC 393, L. paracasei CCUG 32212, L. rhamnosus ATCC 7469, L. zeae CCUG 35515, and 46 clinical strains of L. casei/paracasei/rhamnosus . Inhibitory effect against Streptococcus mutans and acid production were examined. Results revealed that each type species strain and identified clinical isolate showed its own unique DGGE pattern using CARP1-GC and CARP2 primers. HDA1-GC and HDA2 primers could distinguish the strains of L. paracasei from L. casei . It was found that inhibitory effect of L. paracasei was stronger than L. casei and L. rhamnosus . The acid production of L. paracasei was lower than L. casei and L. rhamnosus . In conclusion, the technique has been proven to be able to differentiate between closely related species in L. casei group and thus provide reliable information of their phenotypic appearances.